Creating Sustainable Products - Ries, Lena; Wartzack, Sandro; Zipse, Oliver (Road to Net Zero, 2023)
On the Road to Net Zero, products must not only become CO2-neutral in the consumption phase, but the environmental impact needs to be mitigated from the extraction of the raw materials to their end-of-life disposal. The consideration of the entire life cycle—cradle to cradle—as well as rising consumer demand for sustainable products—requires a new paradigm in product design: Design for circularity. Circular design focuses on developing design strategies that enable circularity, such as material selection, design for disassembly, product lifetime extension strategies, and the design of closed-loop systems. Thus, the first section after the introduction of this chapter (Sect. 5.2) provides an overview of the research field of design for circularity. After reviewing the concept of the circular economy (CE), different frameworks for operationalizing the CE are outlined. Based on this review and discussion, we derive three implications for circular design: a change in product design, a change in service design, and a change in user behavior. Finally, we address the implementation challenges that manufacturing companies face when transitioning to a CE. In the subsequent expert discussion (Sect. 5.3) between Oliver Zipse and Prof.-Ing. Sandro Wartzack, these issues are reflected upon from a practitioner’s perspective. In the final section of this chapter (Sect. 5.4), future avenues of research are presented, and the challenges and opportunities of circular design strategies are discussed.<br
Keywords: Design for circularity; Circular economy; R-strategies; Product life cycle; Product service systems

Das Versprechen nachhaltiger digitaler Dienstleistungen - eine Fallstudie - Ries, Lena; Lugmair, Nina; Kurtz, Julian; Beckmann, Markus; Roth, Angela (Sustainable Service Management, Forum Dienstleistungsmanagement, 2024)

Innovation process design for servitisation: the digital service innovation case at uvex - Kurtz, Julian; Meyer, Patrick; Lugmair, Nina; Ries, Lena; Roth, Angela (Journal of Enterprise Information Management, 2025)
Purpose: The purpose of this study was to increase knowledge of digital service innovation in servitisation by extending design principles and proposing an innovation process design for smart product-service systems (PSS) development. Furthermore, the study addresses the alignment of multiple stakeholders in the development of smart PSS, thereby bridging the gap between theory and practice. Design/methodology/approach: A qualitative 17-month action design research approach was taken. This study designed an innovation process for smart PSS development. For this, different development streams were synchronised and multiple stakeholder perspectives were integrated. Drawing on the socio-technical systems perspective as theoretical lens, the authors utilised knowledge in the field of digital service innovation and servitisation. In multiple iterations, the authors, together with practitioners, explored how best to synchronise different smart PSS development activities to ensure subsequent operations of the system. Findings: The findings of the longitudinal study conducted with the manufacturing firm uvex propose a hybrid stage-gate innovation process design for smart PSS development. An evaluation with several international academics and practitioners enhances the rigour of the innovative approach. Originality/value: The findings contribute to the literature on digital service innovation and servitisation by applying a rarely used socio-technical perspective to innovation process design for smart PSS development. The longitudinal approach over 17 months in a qualitative action design research setting adds to the knowledge base with novel insights from practitioners’ problems.
CRIS-Team Scopus Importer:2025-04-01
Keywords: Action design research; Digital service innovation; Innovation process design; Product-service systems; Servitization; Socio-technical systems

Making Sense of the Sustainable Smart PSS Value Proposition - Lugmair, Nina; Ries, Lena; Schymanietz, Martin; Beckmann, Markus; Roth, Angela (ICIS 2022 Proceedings.3., 2022)
While academia attributes superior value potential to sustainable smart PSS (SSPSS), in practice, they are not widely implemented. To address this gap, we analyze how the notion of SSPSS value is constructed through sensemaking. Adopting a case study approach, we explore differences in organizational sensemaking. Moreover, we analyze how the three functional roles “digital innovation and technology”, “sustainability”, and “market” involved in innovating SSPSS make sense of the value proposition. We conclude that value is subjective and the value proposition of SSPSS is multi-faceted. Each facet is constructed through the interaction of organizational, functional roles’, and individual sensemaking. At the organizational level, commitment, identity, and expectations influence the creation of shared meaning. At the functional role level, actors differ in their sensemaking based on the cognitive frames applied. At the individual level, subjective beliefs impact sensemaking. Hence, sensemaking is a multi-level process that raises the question of alignment.<br

Managing collaboration for servitization – A service ecosystems perspective - Lugmair, Nina; Posselt, Tim; Kurtz, Julian; Ries, Lena; Roth, Angela (33rd International RESER Conference 2023, 2024)

Sustainable smart product-service systems: a causal logic framework for impact design - Ries, Lena; Beckmann, Markus; Wehnert, Peter (Journal of Business Economics, 2023)
Digital technologies can elevate product-service systems (PSS) to smart PSS, which focus on performance rather than ownership and are considered a means for dematerialization. However, transitioning to smart PSS does not guarantee sustainability. To understand the impact of smart PSS holistically, we take a two-pronged approach. First, we use the theory of change to conceptualize the causal link between sustainable smart PSS and their ultimate impact. We develop a three-step causal logic framework consisting of design, causation, and impact. Within this framework, we identify the business model properties of sustainable smart PSS as design characteristics and categorize the eventual impacts based on the triple bottom line. We introduce the term multi-causal pathway to describe the causation processes underlining the possibility of non-linearity and multi-causality. Second, we conduct a systematic literature review to investigate the mechanisms linking design and impact. Based on an analysis of 63 publications, we identify 17 specific mechanisms and group them into four types: information, resource, empowerment, and adverse mechanisms. Visualizing our results, we develop a morphological box as a toolkit for managers to develop their own impact-oriented logic model by identifying and activating the multi-causal pathway that fosters the desired sustainability effects. Moreover, discussing our framework, we develop research propositions and managerial questions for impact design. By linking the theory of change with the business model impact, we contribute toward a conceptual synthesis for understanding the impact of (sustainable) smart PSS.
CRIS-Team Scopus Importer:2023-04-28
Keywords: Business model; Logic model; Morphological box; Product-service system; Smart technology; Sustainability; Theory of change